2013
DOI: 10.1093/jac/dks498
|View full text |Cite
|
Sign up to set email alerts
|

LQB-118, an orally active pterocarpanquinone, induces selective oxidative stress and apoptosis in Leishmania amazonensis

Abstract: Our results suggest that LQB-118 selectively induces ROS-triggered and mitochondria-dependent apoptosis in this parasite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 33 publications
1
42
0
6
Order By: Relevance
“…We also have contributed in the understanding of the cell death mechanism that is induced by LQB-118. We reported that LQB-118 induces ROS production in L. amazonensis promastigotes a few minutes after incubation and it is sustained after 24 h, suggesting that this event is one of the parasite death triggers (13). Increased ROS levels were also found in L. braziliensis promastigotes treated with LQB-118 (12).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We also have contributed in the understanding of the cell death mechanism that is induced by LQB-118. We reported that LQB-118 induces ROS production in L. amazonensis promastigotes a few minutes after incubation and it is sustained after 24 h, suggesting that this event is one of the parasite death triggers (13). Increased ROS levels were also found in L. braziliensis promastigotes treated with LQB-118 (12).…”
Section: Discussionmentioning
confidence: 82%
“…The pterocarpanquinone LQB-118, the lead compound from this class, has antiprotozoal and anti-leukemic cell line activities, even in cells with an multidrug resistance phenotype (8)(9)(10). We have also demonstrated that LQB-118 is effective in treating experimental cutaneous leishmaniasis via oral delivery (11,12), and the death of Leishmania amazonensis parasites involved oxidative stress with hallmarks of apoptosis (13). These results suggest that LQB-118 is a promising lead compound and should be further investigated.…”
mentioning
confidence: 70%
“…Intracellular ATP levels are susceptible to alterations when there is mitochondrial damage, such as changes in the mitochondrial membrane potential and an increase in the levels of reactive oxygen species (51,54). Promastigotes treated with LSPN331 showed a significant decrease in intracellular ATP levels in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar do paládio oferecer a vantagem de ser mais versátil e eficiente em reações de aminação, as reações de acoplamento C-N na presença de sais ou óxidos de cobre em estado de oxidação (I) ou (II) são muito empregadas para a síntese de produtos naturais, pois o cobre é bastante econômico CHEPRAKOV, 2004;DEJON et al, 2013;ZHU et al, 2013b (MAIA et al, 2011;DE SÁ BACELAR et al, 2013;RIBEIRO et al, 2013;COSTA et al, 2014;MARTINO et al, 2014).…”
Section: Reações Em "úNico Pote" Catalisadas Por Cobreunclassified
“…O LQB 118 (93) é uma substância classificada como pterocarpanquinona devido a uma hibridação entre um pterocarpano (pertencente à classe dos isoflavonoídes) e o lapachol (RIBEIRO et al, 2013). Em virtude da potente ação anticâncer do LQB 118 (93), foi desenvolvido o LQB 192 (94), denominado azapterocarpanquinona, na qual foi feita uma troca do grupo oxigênio pelo arilsulfonamida, grupo responsável pela ação biológica de muitos fármacos (BOGEN et al, 2010;BASHIR et al, 2011;DE OLIVEIRA et al, 2011;LUO et al, 2011;YANG et al, 2011;MALWAL et al, 2012;ZOUMPOULAKIS et al, 2012) MALWAL et al, 2012NEITZEL et al, 2011;ZOUMPOULAKIS et al, 2012;AL-DOSARI et al, 2013;GHORAB et al, 2010GHORAB et al, , 2015CARTA et al, 2015;REDDY et al, 2015).…”
Section: Reações Em "úNico Pote" Catalisadas Por Cobreunclassified